Comparison of perfectionism, ego strength, anger, and anger rumination in individuals with major depression and obsessive-compulsive disorder - Mohammad Ali Besharat; Maryam Taheri; Masoud Gholamali LAvasani (Faṣlnāmah-i Farhang Mushavirah va Ravān/Darmānī, 2016)
The main objective of the present study was to compare perfectionism, ego strength, anger, and anger rumination in individuals with major depression (MDD) and obsessive-compulsive disorder (OCD). Tehran Multidimensional Perfectionism Scale (TMPS), Ego Strength Scale (ESS), Tehran Multidimensional Anger Inventory (TMAI), and Anger Rumination Scale (ARS) were completed by 60 patients (39 patients with major depression disorder, 21 patients with obsessive-compulsive disorder). Method of the present descriptive study was causal-comparative and statistical society included all major depressive disordered and obsessive-compulsive disordered patients refering to private clinics in Tehran during the year 1394. Analysis of the data involved both descriptive and inferential statistics including means, standard deviations, correlation coefficient, MANOVA, and independent t-test. The results demonstrated that dimensions of perfectionism were different in MDD and OCD: while self-oriented perfectionism and other-oriented perfectionism were elevated in patients with obsessive-compulsive disorder sample, socially-prescribed perfectionism was elevated in major depression disorder sample. The results revealed no difference between the two groups in ego strength. Ager-in was elevated in major depression disorder sample, and there was no significant difference in other dimensions among the two groups. The results indicated that individuals with MDD showed more level of anger rumination than individuals with OCD. According to the results of the present study it can be concluded that comorbidity of MDD and OCD can be clarified through the common bases of psychopathology, meanwhile different principals of psychopathology justify distinction between the two disorders.